Los Dioses de verdad tienen huesos - Santos, Belen; Alfaro, Davod (Spain, 2011)
The film follows five children with severe health problems in Guinea Bissau as they are “evacuated” to Europe for life saving medical care.
Verzio Film Festival Submission
Keywords: Documentary films